Features of Formation and Realization of Resource Saving Measures Complex Aimed to Solve Social, Ecological and Economic Problems of the Russian Construction Industry - Astaf'eva, Olga; Potapova, Irina (International Review of Management and Marketing, 2016)
This article deals with the ecological aspects of the construction industry, the resource saving and ecological security management issues in construction, operation and maintenance of facilities. Rational natural resource management and resource saving measures may be considered the economic development goals of top priority. In order to effectively tackle the relevant issues, the authors suggest new approaches to forging the resource saving mechanism, including the creation of a national standard based on the international 'green' certification systems in line with the unique features of the Russian construction industry. This mechanism, relying on the world practical and academic experience and supported by the government by means of various incentives and benefits, is intended to become an efficient instrument in settling the environmental issues of the modern construction industry. Keywords: resource saving, mechanism, sustainable development, ecological certification JEL Classifications: P20; Q00; Z13